Respuesta :
Distribute 2 to 3t and 4, and 6 to t and 2
2(3t + 4) = 6t + 8
6(t + 2) = 6t + 12
Combine like terms:
6t + 8 + 6t + 12 = 12t + 20
12t + 20 is your answer
hope this helps
2(3t + 4) + 6(t + 2)
First, distribute. The Distributive Property: a(b + c) = ab + ac. Distribute 2 and 6 to get rid of the parentheses.
2(3t + 4) + 6(t + 2)
6t + 8 + 6(t + 2)
6t + 8 + 6t + 12
Collect like terms (constants and variable terms).
6t + 8 + 6t + 12
12t + 20
The expression now has one variable term and one constant; it cannot be simplified further.
Answer:
12t + 20